2003
DOI: 10.1093/ije/dyg192
|View full text |Cite
|
Sign up to set email alerts
|

Estonia 1989–2000: enormous increase in mortality differences by education

Abstract: Social disruption and increasing inequalities in wealth can be considered main recent determinants; however, causal processes, shaped decades before recent reforms, also contribute to this widening gap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
2
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(100 citation statements)
references
References 20 publications
7
86
2
5
Order By: Relevance
“…This result is also in keeping with the existing research literature as many studies have highlighted the comparatively poor performance of these countries (Bobak, Pikhart, Rose, Hertzman, & Marmot, 2000;Carlson, 1998;Knesebeck, Verde, & Dragano, 2006;Olsen & Dahl, 2007) particularly in terms of mortality (see for example Leinsalu, Vagero, & Kunst, 2003;Mackenbach, 2006;Shkolnikov et al, 2006;Valkonen, 2001). Although the existing research literature on health differences between welfare state regimes is unequivocal on the better performance of the Scandinavian welfare model, and the poorer performance of the Eastern and Southern European countries (Bambra, 2006a;Chung & Muntaner, 2007;Coburn, 2004;Navarro et al, 2006;Olsen & Dahl, 2007); it is less unanimous on the relatively poor performance of the Anglo-Saxon countries.…”
Section: Individuals and Regionssupporting
confidence: 84%
“…This result is also in keeping with the existing research literature as many studies have highlighted the comparatively poor performance of these countries (Bobak, Pikhart, Rose, Hertzman, & Marmot, 2000;Carlson, 1998;Knesebeck, Verde, & Dragano, 2006;Olsen & Dahl, 2007) particularly in terms of mortality (see for example Leinsalu, Vagero, & Kunst, 2003;Mackenbach, 2006;Shkolnikov et al, 2006;Valkonen, 2001). Although the existing research literature on health differences between welfare state regimes is unequivocal on the better performance of the Scandinavian welfare model, and the poorer performance of the Eastern and Southern European countries (Bambra, 2006a;Chung & Muntaner, 2007;Coburn, 2004;Navarro et al, 2006;Olsen & Dahl, 2007); it is less unanimous on the relatively poor performance of the Anglo-Saxon countries.…”
Section: Individuals and Regionssupporting
confidence: 84%
“…Although we are not able to examine trends in educational differentials in mortality in Bulgaria, evidence from Estonia (Leinsalu et al 2003) indicates that life-expectancy differences by educational attainment at age 25 increased rapidly in that country during the 1990s. This increase was brought about by declining mortality at higher levels of education and increasing mortality at lower levels of schooling.…”
Section: Discussionmentioning
confidence: 93%
“…Studies of trends at individual level performed in different European countries have found that the socioeconomic inequalities in IHD mortality tend to increase with time in both sexes. 29,30,32,54 Few ecological studies have analyzed the evolution over time of these inequalities. In the majority of them, increases in socioeconomic inequalities are observed in both sexes.…”
Section: Trends In Socioeconomic Inequalities In Ihd Mortalitymentioning
confidence: 99%